2020
DOI: 10.36834/cmej.68602
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of burnout amongst Canadian Royal College of Physicians and Surgeons of Canada emergency medicine residents

Abstract: Background: In recent years, there has been growing interest in the field of physician wellness and burnout. The prevalence of burnout is non-uniform between medical specialties and is most prevalent amongst emergency medicine physicians. Importantly, burnout can be observed amongst individuals early in their medical careers, including medical students and residents. Despite ample studies in other populations, there is no national perspective of burnout amongst Canadian Royal College of Physicians and Surgeons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In this study, 2.5% of the EM residents reported having suicidal thoughts during the July 2019 to February 2020 academic year (Table 2), which was lower than the rate reported in previous studies. 1,[55][56][57][58][59] Similar to the findings of other work, [60][61][62][63] residents in this study who identified as…”
Section: Suicidal Thoughtssupporting
confidence: 83%
“…In this study, 2.5% of the EM residents reported having suicidal thoughts during the July 2019 to February 2020 academic year (Table 2), which was lower than the rate reported in previous studies. 1,[55][56][57][58][59] Similar to the findings of other work, [60][61][62][63] residents in this study who identified as…”
Section: Suicidal Thoughtssupporting
confidence: 83%
“…Burnout is a complex psychological syndrome characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment (Jonsdottir & Dahlman, 2019). The Maslach Burnout Inventory (MBI) is widely used to measure burnout, assessing these dimensions among medical personnel (Liu et al, 2020). The MBI emphasizes that researchers should treat burnout as continuous data for each domain, discouraging dichotomizing or combining the subscales to label individuals as having burnout (Rotenstein et al, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%